Kombinasi Puding Daun Binahong Dan Accupressure Menurunkan Tekanan Darah Pada Pasien Hipertensi Di Wilayah Kerja Puskesmas Ngemplak Sleman Yogyakarta - Fajarina Lathu Asmarani (HEALTH CARE : JURNAL KESEHATAN, 2021)
Hypertension is one of the most common medical disorders, associated with an increased incidence of death. The Integrated Survey of Diseases in Puskesmas and Hospitals shows that hypertension is a common disease. It is necessary to take control measures through the management of Binahong processed products combined with acupressure. This study aims to scientifically prove the effect of the combination of Binahong Pudding and Accupressure on blood pressure. This type of research was a quasy experiment with pre-test and post-test research designs without control. The research was conducted in July 2019 at Wilayah Kerja Puskesmas Ngemplak Sleman Yogyakarta. with a sample of 44, selected using consecutive sampling. Respondents were given binahong pudding and accupressure for 7 days. Blood pressure was measured using a Digital Tensimeter. Data analysis using the Wilcoxon Test. Blood pressure before intervention was 144.75 / 90.75 mmHg with a standard deviation value of 1.77687. In the post test, the blood pressure was 132 / 85.5 mmHg with a standard deviation value of 0.87067. The p-value is 0.000 <0.05 for both systolic and diastolic blood pressures.The combination of Binahong Pudding and Accupressure has been scientifically proven reduce blood pressure in hypertensive patients at Wilayah Kerja Puskesmas Ngemplak Sleman Yogyakarta